Fe3O4 / multi-walled carbon nanotube composite wave-absorbing filler as well as preparation method and application thereof
By blending Fe3O4 nanoparticles with multi-wall carbon nanotubes and adding chitosan to form a three-dimensional network structure, the existing absorbing filler has been solved, and lightweight and efficient absorption is achieved Composite wave absorbing filler with wave performance, suitable for military stealth coating materials.
Patent Information
- Application Number
- CN202411559729.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-04
AI Technical Summary
In industrial applications, existing wave absorbing fillers have problems such as large weight, poor dispersion, narrow absorption frequency band and unenvironmental production process, which are difficult to meet the stealth needs of military weapons and equipment and flight devices.
By blending Fe3O4 nanoparticles with multi-walled carbon nanotubes (MWCNTs) and adding chitosan to the synthesis of composite fillers, a stable three-dimensional network structure is formed, which improves the dispersion and absorption performance of the wave absorbing fillers.
The Fe3O4/MWCNTs composite absorbing filler that achieves lightweight and efficient wave absorption performance simplifies the production process and reduces the impact on the environment. It is suitable for stealth coating materials for military weapons and equipment and flight devices.
Smart Images

Figure CN119432036A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of material preparation, and specifically relates to a Fe 3 O 4 / Multi-walled carbon nanotube composite absorbing filler and its preparation method and application. Background Art
[0002] In modern warfare, countries around the world attach great importance to improving the survival, penetration and deep strike capabilities of weapons and equipment. With the rapid development of detection technology and precision-guided weapons, once weapons and equipment are discovered by the detection system, it may bring fatal consequences. In order to improve the hiding ability of military weapons and equipment and flying devices, stealth technology has become the key to solving the problem. Stealth technology refers to the technology that can avoid radar and other detection methods in a small range. However, the key to stealth technology lies in the technology of absorbing materials. Absorbing materials can be divided into coating type and structural type. Coating type absorbing materials have the advantages of simple preparation process and low cost. Therefore, the use of absorbing coatings can enable aircraft to obtain radar stealth performance. In absorbing coatings, electromagnetic wave absorber fillers play a major role in loss, so the research of new high-efficiency absorbers is the focus and difficulty.
[0003] According to the different mechanisms, the absorbers can be divided into electric loss absorbers and magnetic loss absorbers. However, it is difficult for a single type of absorber to achieve the ideal absorbing effect. Therefore, the electric loss absorber and the magnetic loss absorber are combined to improve the absorbing performance of the composite material by combining two different absorbing mechanisms. 3 O 4 Composite absorbing filler. Fe 3 O 4 It is the main component of magnetite, belongs to the cubic crystal system, and has an inverse spinel structure. 3 O 4 In the crystal, oxygen atoms are densely packed in cubic form, and iron atoms occupy the gaps between tetrahedrons and octahedrons. 3+ Occupies tetrahedral gaps, while octahedral gaps have Fe 2+ and Fe 3+ Based on this special crystal structure, Fe 3 O 4 It has both magnetic loss and dielectric loss for electromagnetic waves, thus showing good electromagnetic wave absorption performance in certain specific frequency bands. 3 O 4Nanoparticles have shown many excellent characteristics, such as large specific surface area, high magnetic strength and good paramagnetism. MWCNTs are tubular structures formed by curling up multiple layers of graphite, and have unique electrical properties. They have low production costs, are easy to mass produce and have high chemical stability. Therefore, MWCNTs are widely used in the field of electromagnetic shielding. The carbon atoms in carbon nanotubes are sp 2 Hybridization is the main feature, with high conductivity, light weight, extremely high aspect ratio and high mechanical strength. Its application in polymer-based electromagnetic shielding materials has obvious advantages. When the content in the polymer matrix is relatively low, a higher electromagnetic shielding efficiency can be obtained. However, when the above two materials are used as absorbing fillers alone, it is difficult to achieve the current comprehensive performance indicators of absorbing fillers. The reason is that the single component Fe 3 O 4 The density is relatively large, and single-component MWCNTs require cumbersome surface modification to improve their dispersibility in the polymer matrix, and their narrow absorption band limits their large-scale application in the industrial field.
[0004] CN 102350282 A discloses a method for preparing a cobalt-nickel ferrite / multi-walled carbon nanotube magnetic nanocomposite material. The nanocomposite material prepared by acidifying MWCNTs has good dispersion and is not easy to agglomerate. However, when acidifying MWCNTs, a strong oxidizing concentrated acid is used, and the acidification time is long, which is not conducive to industrial production. CN 101320607B discloses a method for preparing Fe by alcohol thermal method. 3 O 4 / MWCNTs magnetic nanocomposites, and the acid treatment of MWCNTs enhances the bonding with Fe 3 O 4 The binding effect of Fe 3 O 4 The chitosan added to the system is not only non-toxic and harmless, but also can play a "bridging" role to make Fe 3 O 4 Tightly wrapped around the surface of MWCNTs, forming a stable three-dimensional network structure. CN 103435972 A relates to a preparation method of a nickel-zinc ferrite-multi-walled carbon nanotube-epoxy resin composite material, which requires the use of a strong acid to acidify the multi-walled carbon nanotubes for a long time to achieve the purpose of modification; and the process of separating and purifying the nickel-zinc-iron / MWCNTs composite powder has problems such as complex process and the use of toxic reagents, which is not conducive to large-scale environmentally friendly production.
[0005] Therefore, how to provide a Fe 3 O 4 / Multi-walled carbon nanotube composite absorbing filler is a technical problem that needs to be solved urgently by technicians in this field. Summary of the invention
[0006] In view of this, in order to solve the problems of high toxicity of the used agents, poor binding effect, and being unfavorable for industrial production, the present invention discloses a Fe 3 O 4 / Multi-walled carbon nanotube composite absorbing filler and preparation method thereof, the filler is a MWCNTs / Fe containing both electrical loss type absorbing material and magnetic loss type absorbing material 3 O 4 Composite absorbing filler.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] The first technical purpose of the present invention is to provide a Fe 3 O 4 / A method for preparing a multi-walled carbon nanotube composite wave absorbing filler, the method specifically comprising the following steps:
[0009] ① Add ethylene glycol, FeCl 3 6H 2 O, MWCNTs and chitosan were ultrasonically stirred at room temperature and the reaction time was started;
[0010] ② After the timing reaction of step ① is completed, polypropylene glycol 2000 (PPG2000) and sodium acetate (NaAc) are added into the system and ultrasonic stirring is continued to start the timing reaction;
[0011] ③ After the timing reaction in step ② is completed, the reaction solution is transferred into the polytetrafluoroethylene lining of the reaction kettle and placed in a box-type atmosphere furnace for thermal reaction timing treatment;
[0012] ④ After the heat reaction timing treatment in step ③ is completed, pour it into a beaker and let it stand after cooling to room temperature (25°C). After standing and stratification, pour out the supernatant and wash it repeatedly with anhydrous ethanol and deionized water to remove impurities;
[0013] ⑤ Separate the product by suction or filtration;
[0014] ⑥Put the filter cake of step ⑤ into a vacuum drying oven for drying and dehydration to obtain the target product MWCNTs / Fe 3 O 4 Composite absorbing material.
[0015] Optionally, the method further comprises removing water from the raw material: removing FeCl 3 6H 2O, MWCNTs, sodium acetate (NaAc) and chitosan are dried under vacuum conditions at 70-90° C. for 2-3 hours to remove moisture from the solid raw materials.
[0016] Furthermore, the raw material dehydration is carried out in a vacuum drying oven, the vacuum drying temperature is 70-90°C, the vacuum pressure is -0.08 to -0.10Mpa, and the drying time is 2-3h.
[0017] Optionally, in step ①, ethylene glycol, FeCl 3 6H 2 The order of adding O, MWCNTs and chitosan was to first add 140 ml of ethylene glycol, then add the ground FeCl 3 6H 2 O powder and MWCNTs, and finally chitosan powder was added and reacted with ultrasonic stirring for 1-1.5h.
[0018] Optionally, in step ⑤, the product is separated by suction filtration or filtration, and the product is washed with anhydrous ethanol 3-5 times to remove PPG2000 in the product, and then washed with pure water.
[0019] Optionally, in step ③, the vacuum drying temperature is 160-190° C., the vacuum pressure is -0.08 to -0.10 MPa, and the drying time is 10-12 h.
[0020] Optionally, in step ⑥, the vacuum drying temperature is 70-90°C, the vacuum pressure is -0.08 to -0.10 MPa, and the drying time is 1-2 h.
[0021] Optionally, the reaction time in step ② is 0.5-1h.
[0022] It should be noted that MWCNTs have the characteristics of light weight, large specific surface area, excellent electrical and thermal conductivity, and can achieve high electromagnetic shielding effectiveness when the content in the polymer matrix is relatively low. However, from the perspective of the design of absorbing fillers, adding carbon nanotubes alone to the resin matrix cannot achieve good dispersion and has no magnetic properties, which limits the further improvement of its absorbing performance. Moreover, the single component Fe 3 O 4 Nanoparticles are also difficult to achieve the comprehensive performance indicators of current electromagnetic shielding functional materials. In order to improve the single component MWCNTs and Fe 3 O 4 The electromagnetic wave absorption performance of the polymer composite material is improved by combining the two and utilizing their synergistic effect.
[0023] In order to improve the absorbing performance of polymer-based absorbing composite materials, there are mainly the following methods: 1) Adjust the content of electric loss type absorber or magnetic loss type absorber in the resin matrix. 2) Fill two or more absorbing materials of the same loss type. 3) Compound two or more absorbing materials of different loss types. The existing methods have the following problems: 1) Using a single loss type and a single type of absorbing material may increase the weight of the absorbing composite material, and it is difficult to achieve the ideal absorbing effect. 2) Filling two or more absorbing materials of the same loss type can increase the effective absorption bandwidth and improve the absorbing effect to a certain extent. However, it is difficult to improve the problem that some magnetic loss absorbers have high density and heavy weight. 3) Compounding two or more absorbing materials of different loss types can make the composite material have both electric loss and magnetic loss for electromagnetic waves, such as compounding carbon material (electric loss type absorbing material) and ferromagnetic material (magnetic loss absorbing material).
[0024] However, the existing methods do not achieve a simple, environmentally friendly and effective composite process. Highly corrosive reagents are used in the composite process and some of the treatment processes are cumbersome. After the composite, the situation of "1+1<2" may occur, that is, the two materials may destroy each other's structure, inhibit grain growth, and fail to achieve ideal adhesion or overlap during the composite process. At the same time, the composite fillers prepared by the existing methods have not been widely used in the field of electromagnetic wave absorption.
[0025] The present invention blends carbon nanotubes with magnetic fillers, and chitosan added during the synthesis of the composite filler can play a "adhesion" role. 3 O 4 The "bridge" between the microspheres and MWCNTs is built to achieve the orderly spatial morphology between the magnetic microspheres and the conductive carbon tubes, and finally the electromagnetic properties of the absorbing filler are adjusted by regulating the microscopic morphology, and a structural and performance regulation scheme is established. The composite of the two fillers not only improves the dispersion of carbon nanotubes, but also 3 O 4 The nanoparticles provide effective hysteresis loss, thereby improving the electromagnetic wave absorption performance; and the effective composite lightweight of the two fillers improves the problems of heavy weight of tightly stacked materials and easy deposition during the application of coating materials.
[0026] The second technical purpose of the present invention is to provide a Fe 3 O 4 / Multi-walled carbon nanotube composite absorbing filler.
[0027] The third technical purpose of the present invention is to provide a Fe 3 O 4 / Application of multi-walled carbon nanotube composite absorbing fillers in military weapons and equipment.
[0028] Specifically, Fe prepared according to the above method 3 O 4 / Application of multi-walled carbon nanotube composite absorbing fillers in stealth of fighter jets and ships.
[0029] Furthermore, the Fe 3 O 4 / Application of multi-walled carbon nanotube composite absorbing filler in absorbing coating.
[0030] With the rapid development of detection technology, weapons and equipment are facing more stringent service conditions, and the requirements for radar absorbing coatings are also put forward as "thin, light, wide and strong". 3 O 4 Composite absorbing fillers have excellent absorption performance and are conducive to the lightweight design of absorbing materials, which can meet the above requirements. 3 O 4 On the one hand, the combination of nanoparticles and MWCNTs can obtain the characteristics of the two components, thus improving their comprehensive performance. On the other hand, the "collision" and combination of the two components can create some new structures, interfaces and bridges, which are conducive to the absorption of electromagnetic waves. And by adjusting the content of MWCNTs, the electromagnetic parameters of the absorbing filler can be effectively adjusted, and then the absorbing performance of the absorbing coating can be adjusted.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1) The present invention discloses a simple one-step solvothermal method for preparing MWCNTs / Fe 3 O 4 Nanocomposite filler, and the process is simple, which is conducive to mass preparation and production.
[0033] 2) The nanocomposite filler forms a unique three-dimensional network structure. 3 O 4 In nanocomposite fillers, Fe 3 O 4 The composite of nanoparticles and MWCNTs is relatively uniform without agglomeration, and the interface and bridging structures at the connection between the two can better assist the material in absorbing electromagnetic waves.
[0034] 3) Due to the pure MWCNTs sample and Fe 3 O 4 The absorption performance of pure samples and their simple physical blends is not ideal, while the MWCNTs, Fe 3 O 4 The structure of the nanocrystal junction has a strong interaction, and the charge can easily pass through the junction from Fe3 O 4 When transferred to MWCNTs, the hybrid structure of the two is beneficial to the dipole interaction of the composite material, thereby improving the microwave absorbing performance of the composite material.
[0035] 4) The present invention meets the requirement of "lightness" of new wave-absorbing materials. The density of MWCNTs is relatively low, which is conducive to the "lightness" of wave-absorbing composite materials and provides ideas for the preparation of lightweight wave-absorbing coatings.
[0036] 5) The present invention can effectively adjust the MWCNTs / Fe ratio by adjusting the content of MWCNTs. 3 O 4 The complex dielectric constant of the nanocomposite material can effectively adjust the absorbing properties of the absorbing coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0038] Figure 1 MWCNTs / Fe prepared in (a) Example 1, (b) Example 2, (c) Example 3 3 O 4 Scanning electron microscope image of the composite absorbing material.
[0039] Figure 2 MWCNTs / Fe prepared in Example 3 3 O 4 EDS surface scanning energy spectrum of composite absorbing materials, including C, Fe and O elements.
[0040] Figure 3 MWCNTs / Fe prepared in Examples 1, 2, and 3 3 O 4 Infrared spectrum of composite absorbing material.
[0041] Figure 4 MWCNTs / Fe prepared in comparison with Example 1 and Example 3 3 O 4 Electromagnetic parameter diagram of composite absorbing material.
[0042] Figure 5 MWCNTs / Fe prepared in Example 3 (5 mm) 3 O 4 Reflection loss plot of composite absorber material. DETAILED DESCRIPTION
[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.
[0045] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.
[0046] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.
[0047] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.
[0048] The invention discloses a Fe 3 O 4 / Multi-walled carbon nanotube composite wave absorbing filler and preparation method thereof
[0049] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as limiting the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.
[0050] Examples 1-3
[0051] Examples 1-3 of the present invention disclose Fe 3 O 4 and MWCNTs / Fe 3 O 4 The preparation technology comprises the following steps:
[0052] ① FeCl 3 6H 2 O, MWCNTs, NaAc and chitosan were dried under vacuum at 80 °C for 2-3 h to remove water from the solid raw materials;
[0053] ② First add 140mL of ethylene glycol to the 250mL three-necked flask, then add FeCl 3 6H 2 O, MWCNTs and chitosan;
[0054] ③Ultrasonic stirring at room temperature for 1h;
[0055] ④ After the timed reaction is completed, add PPG2000 and NaAc into the three-necked flask and continue ultrasonic stirring for 0.5h;
[0056] ⑤ After the timed reaction is completed, turn off the ultrasound and stirring, transfer the reaction solution into the polytetrafluoroethylene liner of the reactor, and place it in a vacuum drying oven. The vacuum drying temperature is 180°C, the vacuum pressure is -0.08 to -0.10Mpa, and the drying time is 12h;
[0057] ⑥ After the timed reaction is completed, the product is poured out and allowed to stand after cooling to room temperature, and then washed several times with anhydrous ethanol and deionized water to remove impurities;
[0058] ⑦ Separate the product by filtration;
[0059] ⑧Put the filter cake into a vacuum drying oven for drying and dehydration. The vacuum drying temperature is 80°C, the vacuum pressure is -0.08 to -0.10 MPa, and the drying time is 1 h to obtain the target product MWCNTs / Fe 3 O 4 Composite absorbing material.
[0060] Comparative Example 1-2 was used to verify the example from two aspects: whether MWCNTs were added and whether chitosan was added.
[0061] The raw material ratios and preparation conditions in Examples 1-3 and Comparative Examples 1-2 are shown in Table 1.
[0062] Table 1 Raw material ratios and preparation conditions of Examples 1-3 and Comparative Examples 1-2
[0063]
[0064] To further demonstrate the beneficial effects of the present invention and to better understand the present invention, the following experimental examples are used to further illustrate the technical features disclosed in the present invention, but they should not be construed as limiting the present invention. Other improvements made by those skilled in the art based on the above invention content without inventive work are also considered to fall within the scope of protection of the present invention.
[0065] Comparative Example 1 is a pure Fe prepared without MWCNTs and chitosan. 3 O 4 In the preparation process, after ultrasonic stirring, the reaction solution is yellow-brown, and the final product is reddish-brown powder after being placed in a reactor for high-temperature reaction and washing and drying.
[0066] Comparative Example 2 is a Fe-based composite prepared without MWCNTs and containing chitosan. 3 O 4 In the preparation process, after ultrasonic stirring, the reaction solution is yellow-brown, and the final product is black powder after being placed in a reactor for high-temperature reaction and washing and drying.
[0067] Example 1, Example 2, and Example 3 are MWCNTs / Fe prepared with different MWCNTs content ratios. 3 O 4 Composite absorbing material. Preparation process After ultrasonic stirring, the three reaction solutions were dark green. After being placed in a reactor for high-temperature reaction and washed and dried, the final products were all black powders. The SEM (scanning electron microscope) image of the sample shows that in the obtained composite absorbing material, Fe 3 O 4 The microspheres are regular spherical and densely loaded on the surface of CNT. Through measurement, the diameter of the microspheres is about 160-267nm, with small particle size and large specific surface area. At the same time, it can be found that some spherical particles are wrapped around CNT like "sugar gourd strings", forming a stable three-dimensional network structure. And no free Fe was observed in the sample. 3 O 4 Nanoparticles. The above analysis shows that Fe 3 O 4 Nanoparticles were successfully loaded on the surface of MWCNTS.
[0068] And, if Figure 2 As shown, the MWCNTs / Fe prepared in Example 3 3 O 4 In the EDS spectrum of the composite absorber, the N element is evenly distributed in the composite absorber, proving that chitosan is 3 O 4 Evenly distributed in the composite absorbing material.
[0069] according to Figure 4As can be seen from (ab), the electromagnetic parameters of the samples prepared in Example 3 and Comparative Example 1 make the test results significantly different. The ε' of Example 3 increases from 4.64-9.97 to 8.27-16.51, and the ε" increases from 1.56-2.69 to 2.12-4.8, indicating that the introduction of MWCNTs can significantly improve the dielectric loss of the composite filler. Figure 4 (cd) It can be seen that due to the addition of MWCNTs, the real part of the complex permeability increases in most frequency bands, and the imaginary part of the complex permeability decreases relatively in most frequency bands. μ" increases from -0.29 to -0.05 to -0.06 to 0.046 in 13.41-18 GHz, indicating that the addition of non-magnetic MWCNTs will reduce Fe 3 O 4 Magnetic loss performance, but in the Ku band (12GHz-18GHz), the magnetic loss increases, which is mainly due to the Fe 3 O 4 Interfacial polarization between nanoparticles and MWCNTs and Fe 3 O 4 The interfacial polarization between MWCNTs and Fe 3 O 4 Nanoparticles can improve the magnetic loss characteristics of composite fillers in the form of synergistic enhancement, which is beneficial to the improvement of wave absorption properties.
[0070] In summary, the addition of MWCNTs increases the imaginary part of the complex dielectric constant of the composite absorbing filler, and the dielectric loss of the composite filler increases accordingly, which provides a good electrical loss basis for the absorbing characteristics of the composite filler. 3 O 4 Nanoparticles can provide magnetic loss for composite fillers, and the "bridging" effect of chitosan can enhance the magnetic field between MWCNTs and Fe 3 O 4 The interface polarization between the two materials is enhanced. In the Ku band, the enhanced interface polarization can increase the magnetic loss of the composite filler, which provides a good magnetic loss basis for the wave absorption characteristics of the composite filler. 3 O 4 The composite filler has a structural basis that exhibits excellent wave absorbing properties.
[0071] The reflection loss test results can reflect the wave-absorbing properties of the material. The lower the reflection loss value, the higher the degree of electromagnetic wave absorption of the test sample. The reflection loss frequency can be used to evaluate the application field of the wave-absorbing material. The wave-absorbing filler with outstanding wave-absorbing properties in the frequency range of X-band and Ku-band (12GHz-18GHz) is mainly used for stealth coating materials. According to the reflection loss spectrum, it can be seen that the reflection loss of Example 3 in the frequency bands of 3.96-5.43GHz and 13.8-15.84GHz is lower than -10dB, and the reflection loss bandwidth below -10dB is 3.51GHz, indicating that the composite filler has a high degree of absorption of electromagnetic waves in a wide frequency range (absorption degree can be >90%). Therefore, the wave-absorbing filler is expected to be used in stealth coating materials for fighters and ships.
[0072] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a Fe3O4 / multi-walled carbon nanotube composite absorbing filler, characterized in that: The method specifically comprises the following steps: ① Stir ethylene glycol, FeCl3·6H2O, MWCNTs and chitosan under ultrasonic conditions at room temperature and start the timing reaction; ② After the timing reaction of step ① is completed, polypropylene glycol 2000 (PPG2000) and sodium acetate (NaAc) are added into the system and ultrasonic stirring is continued to start the timing reaction; ③ After the timing reaction in step ② is completed, the reaction solution is transferred into the polytetrafluoroethylene lining of the reaction kettle and placed in a box-type atmosphere furnace for thermal reaction timing treatment; ④ After the heat reaction timing treatment in step ③ is completed, cool to room temperature (25°C) and let stand, after standing and stratification, pour out the supernatant, and use anhydrous ethanol and deionized water to repeatedly wash to remove impurities; ⑤ Separate the product by suction or filtration; ⑥ Dry the filter cake in step ⑤ to remove water, and obtain the target product MWCNTs / Fe3O4 composite absorbing material.
2. The method for preparing the Fe3O4 / multi-walled carbon nanotube composite wave absorbing filler according to claim 1, characterized in that: The method further comprises removing water from the raw materials: placing FeCl3·6H2O, MWCNTs, sodium acetate (NaAc) and chitosan under vacuum conditions of 70-90°C and drying for 2-3 hours to remove water from the solid raw materials.
3. The method for preparing the Fe3O4 / multi-walled carbon nanotube composite wave absorbing filler according to claim 2, characterized in that: The raw material dehydration is carried out in a vacuum drying oven, the vacuum drying temperature is 70-90°C, the vacuum pressure is -0.08 to -0.10Mpa, and the drying time is 2-3h.
4. The method for preparing the Fe3O4 / multi-walled carbon nanotube composite wave absorbing filler according to claim 1, characterized in that: In step ①, the order of adding ethylene glycol, FeCl3·6H2O, MWCNTs and chitosan is to first add 140 ml of ethylene glycol, then add the ground FeCl3·6H2O powder and MWCNTs, and finally add chitosan powder, and react with ultrasonic stirring for 1-1.5 hours.
5. The method for preparing the Fe3O4 / multi-walled carbon nanotube composite wave absorbing filler according to claim 1, characterized in that: In step ③, the vacuum drying temperature is 160-190°C, the vacuum pressure is -0.08 to -0.10Mpa, and the drying time is 10-12h.
6. The method for preparing the Fe3O4 / multi-walled carbon nanotube composite wave absorbing filler according to claim 1, characterized in that: In step ⑤, the product is separated by suction filtration or filtration, and the product is washed with anhydrous ethanol 3-5 times to remove PPG2000 in the product, and then washed with pure water.
7. The method for preparing the Fe3O4 / multi-walled carbon nanotube composite wave absorbing filler according to claim 1, characterized in that: In step ⑥, the vacuum drying temperature is 70-90°C, the vacuum pressure is -0.08 to -0.10Mpa, and the drying time is 1-2h.
8. The method for preparing the Fe3O4 / multi-walled carbon nanotube composite wave absorbing filler according to claim 1, characterized in that: The reaction time in step ② is 0.5-1h.
9. A Fe3O4 / multi-walled carbon nanotube composite absorbing filler prepared by the method as claimed in claim 1.
10. Use of the Fe3O4 / multi-walled carbon nanotube composite absorbing filler prepared by the method of claim 1 in military weapons and equipment.
Citation Information
Patent Citations
Preparation method of chitosan modification barium ferrite filling multi-walled carbon nanotube / poly 3-methylthiophene composite wave-absorbing material
CN102627834A
One-step hydrothermal method for preparing ultrathin Fe3O4 / CNTs (carbon nanotubes) composite wave-absorbing nanomaterial with high absorbability
CN109439280A
Surface Treatment Method of Stainless Steel Plate for Using FPCB Reinforcement
KR1020200131377A
Preparation and use of magnetic polymer nanocomposites
US20160001263A1